2009
DOI: 10.1136/bjo.2009.166975
|View full text |Cite
|
Sign up to set email alerts
|

Current treatment options for retinal angiomatous proliferans (RAP)

Abstract: Retinal angiomatous proliferation (RAP) accounts for 12-15% of all patients with neovascular age-related macular degeneration (NV-AMD). However, this subtype is often excluded from clinical trials aimed at assessing the efficacy of various treatment options for NV-AMD. Thus, there are no established protocols for the management of RAP. This review of current literature on RAP compares the outcomes of various treatment options for this condition and highlights the lack of clinical trials and paucity of long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 39 publications
(23 reference statements)
1
19
0
2
Order By: Relevance
“…Retinal angiomatous proliferation (RAP), also known as type 3 neovascularization, is a well-recognized neovascular phenotype of age-related macular degeneration (AMD), accounting for 12-15% of its exudative form in Caucasians [1]. The angioproliferative process associated with RAP diverges from other neovascular membranes, as it is believed to start deeply within the retina [2,3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinal angiomatous proliferation (RAP), also known as type 3 neovascularization, is a well-recognized neovascular phenotype of age-related macular degeneration (AMD), accounting for 12-15% of its exudative form in Caucasians [1]. The angioproliferative process associated with RAP diverges from other neovascular membranes, as it is believed to start deeply within the retina [2,3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Reports on intravitreal (IV) ranibizumab, either in monotherapy or with concomitant photodynamic therapy (PDT), have underlined the responsiveness of RAP lesions to both treatment modalities [18,19,20,21]. However, standard protocols for the management of the disease are currently not available [1], and published data are limited to small case series with short follow-up periods [18,19,20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported a poor response to PDT monotherapy in patients with RAP lesions 6,7. Hence, it is common to perform PDT combined with intravitreal injections of triamcinolone acetonide (IVT) or anti-VEGF therapy for RAP 8,9. Several studies were conducted to address the comparative effectiveness between PDT monotherapy and the combination of PDT with IVT or anti-VEGF therapy against RAP lesions, but their conclusions were not consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Hierbei entstammt die neovaskuläre Membran nicht primär der Choriokapillaris, sondern breitet sich entgegengerichtet, aus den retinalen Gefäßen entspringend, Richtung Choroidea aus [3]. Bezüglich des am besten geeigneten therapeutischen Vorgehens ist bei dieser, auch als Typ-3-Neovaskularisation bezeichneten Form aktuell kein Goldstandard etabliert [3,4].…”
unclassified